Efficacy and Compatibility Test of Pseudomonas fluorescens with Fungicides Pyraclostrobin and Fluxapyroxad Against Alternaria solani in Tomato Plants - Hardiana, Sindy Sukma; Abadi, Abdul Latief (Journal of Tropical Plant Protection, 2025)
Early Blight disease is an important disease of tomato plants caused by the fungus Alternaria solani. This disease attack can cause a decrease in production yields up to 78%. Control efforts using synthetic fungicides continuously can cause new problems for the environment. This research was conducted to determine the effect of fungicide applications with active ingredients Pyraclostrobin+Fluxapyroxad and the addition of biological agent Pseudomonas fluorescens on early blight disease and growth of tomato plants. This study consisted of in vivo and in vitro studies with observation parameters in the form of compatibility of bacteria with fungicides, fungicide inhibition, disease intensity, level of efficacy, and growth of tomato plants. The results showed that the combination of synthetic fungicide and Pseudomonas fluorescens was classified as compatible and effective in controlling Alternaria solani and able to support the growth of tomato plants. Combination treatment can reduce the use of synthetic fungicide by 25% of the recommended dose and is able to give results that are not significantly different from the recommended dose of synthetic fungicide treatment.